Pancreatoduodenectomy with portal vein resection for distal cholangiocarcinoma. Issue 11 (7th August 2017) - Maeta, T; Ebata, T; Hayashi, E; Kawahara, T; Mizuno, S; Matsumoto, N; Ohta, S; Nagino, M; Aoba, T; Kaneoka, Y; Arai, T; Shimizu, Y; et al.
Abstract: Background: Little is known about the value of portal vein (PV) resection in distal cholangiocarcinoma. The aim of this study was to evaluate the clinical significance of PV resection in distal cholangiocarcinoma. Methods: Patients who underwent pancreatoduodenectomy (PD) for distal cholangiocarcinoma between 2001 and 2010 at one of 31 hospitals in Japan were reviewed retrospectively with special attention to PV resection. Short- and long-term outcomes were evaluated. Results: In the study interval, 453 consecutive patients with distal cholangiocarcinoma underwent PD, of whom 31 (6·8 per cent) had combined PV resection. The duration of surgery (510 versus 427 min; P = 0·005) and incidence of blood transfusion (48 versus 30·7 per cent; P = 0·042) were greater in patients who had PV resection than in those who did not. Postoperative morbidity and mortality were no different in the two groups. Several indices of tumour progression, including high T classification, lymphatic invasion, perineural invasion, pancreatic invasion and lymph node metastasis, were more common in patients who had PV resection. Consequently, the incidence of R1/2 resection was higher in this group (32 versus 11·8 per cent; P = 0·004). Survival among the 31 patients with PV resection was worse than that for the 422 patients without PV resection (15 versus 42·4 per cent at 5 years; P < 0·001). Multivariable analyses revealed that age, blood loss, histological grade, perineural invasion, pancreatic invasion, lymph node metastasis and surgical margin were independent risk factors for overall survival. PV resection was not an independent risk factor. Conclusion: PV invasion in distal cholangiocarcinoma is associated with locally advanced disease and several negative prognostic factors. Survival for patients who have PV resection is poor even after curative resection. Abstract : Poor survival despite portal vein resection